Does transition to retirement increase frequence of volunteering: Findings from the Survey of Health, Ageing and Retirement in Europe - Tanskanen Antti O.; Hämäläinen Hans; Arpino Bruno; Solé-Auró Aïda; Danielsbacka Mirkka (Turun yliopisto, 2022)
Objectives Several studies have shown that retired older adults volunteer more than their working counterparts. However, there is a lack of research detecting whether the transition to retirement increases the frequency of volunteering over time and the extent to which this potential effect of retirement varies between sociodemographic groups. Methods We used seven waves of data from the longitudinal Survey of Health, Ageing and Retirement in Europe, collected between 2011 and 2018 from 19 countries. Within-person (or panel fixed-effect) regression models, which considered individual variations and person-specific changes over time, were conducted. Results Transition to retirement over time was associated with an increased frequency of volunteering among older Europeans. In addition, transition to retirement was more strongly associated with volunteering in countries with higher overall rates of volunteering, among more highly educated individuals, and among more religious people. Discussion Our findings supported the impact of time substitution and the centrality of social norms in shaping individual behavior. However, we were unable to find support for an influence of social tie replacement. Overall, transition to retirement tends to open up new ways to organize everyday life and increases the time spent volunteering among older Europeans.